Growth rate and stable carbon and nitrogen isotope trophic discrimination factors of lion and leopard whiskers. (11th December 2017) - Mutirwara, Ruwimbo; Radloff, Frans G.T.; Codron, Daryl
Abstract : Rationale: Stable isotope analysis (SIA) of whiskers has been used to identify temporal feeding habits, intra‐population diet variation, as well as individual dietary specialisation of marine and terrestrial carnivores. However, the potential of the method to disclose such dietary information for large wild felids is hampered by lack of information on species‐specific whisker growth rates, whisker growth patterns and whisker‐diet trophic discrimination factors (TDFs). Methods: Whisker growth rates and growth patterns were measured for four lions ( Panthera leo ) and one leopard ( Panthera pardus ) held at the National Zoological Gardens, Pretoria, South Africa. Actively growing whiskers of the felids were 'marked' four times over 185 days using 13 C‐depleted, C3 ‐based giraffe ( Giraffa camelopardalis ) meat. The periods with low δ 13 C values, identified following serial sectioning of the regrown whiskers at 1 mm intervals and isotopic analysis, were then correlated to specific giraffe meat feeding bouts and hence growth periods. δ 13 C and δ 15 N whisker‐diet TDFs were estimated for five lions whose diet remained consistent over multiple years. Results: The whisker growth rates of three lionesses and the leopard were similar (mean = 0.65 mm day −1 ), despite species, sex and age differences. There was a decrease in whisker growth rate over time, suggesting a non‐linear whisker growth pattern. However, linear and non‐linear growth simulations showed slight differences between the two growth patterns for the proximal 50 mm of whiskers. δ 13 C and δ 15 N lion whisker‐diet TDFs were also similar amongst individuals (mean = 2.7 ± 0.12 ‰ for δ 13 C values and 2.5 ± 0.08 ‰ for δ 15 N values), irrespective of age and sex. Conclusions: The whisker growth rate and δ 13 C and δ 15 N lion whisker‐diet TDFs obtained in this study can be applied in future studies to assign dietary information contained in analysed felid whiskers to the correct time period and improve deductions of prey species consumed by wild felids.